Manaqib Writing in the Circle of the Tariqa Qadiriyya wa Naqsyabandiyyah: A Study on Muhammad Siddiq al-Salihiâs Nayl al-Amani - Widiyanto, Asfa (Center for Research and Development of Religious Literature and Heritage, 2015)
The manaqib of âAbd al-Qadir al-Jilani is of particular importance in the circle of the Tariqa Qadiriyya wa Naqsyabandiyyah (TQN). Some leaders of the TQN have done their best to give a translation and explanation of this manaqib. For instance, Muhammad Siddiq al-Salihi composed a work titled Nayl al-amÄnÄ« fÄ« dhikr manaqib al-quá¹b al-rabbÄnÄ« sayyidinÄ al-shaykh âAbd al-QÄdir al-JÄ«lanÄ«. Another leader, Muslih ibn âAbd al-Rahman al-Maraqi, wrote a treatise titled al-NÅ«r al-burhÄnÄ« fÄ« tarjamat al-lujayn al-dÄnÄ« fÄ« dhikr nubdhah min manaqib al-shaykh âAbd al-QÄdir al-JÄ«lanÄ«. The TQN master Nawawi Siddiq al-Zarkashi wrote a treatise titled Fuyuá¸Ät al-rabbÄnÄ« fÄ« kayfÄ«yÄt qirÄâat manaqib sulá¹Än al-awliyÄâ al-shaykh muá¸¥yÄ« al-dÄ«n âAbd al-QÄdir al-JÄ«lanÄ«. This paper will pay particular attention to the Nayl al-amani, since this work is relatively unknown in Indonesian academia. This book is written in standard Arabic, something which is nowadays rare in the Pesantren and tariqa scholarship. This book is read during the monthly communal ritual of the TQN in the Pesantren Manbaâ al-Falah, Dawe, Kudus, Central Java. This paper strives to unravel the narratives of hagiography in Nayl al-amani and also highlight the uniqueness of Nayl al-amani, most particularly in comparison with the two manaqib writings in the circle of the TQN in Central Java.